Enhancing Wealth Distribution Literacy Based on Mawaris Principles among Urban Muslim Families - Rofiqo, Azidni; Nurafini, Fira; Canggih, Clarashinta; Rohmaningtyas, Nurwinsyah; Kurniawan, Taufiq (FEBI UIN Sunan Kalijaga Yogyakarta, 2026)
The low level of wealth distribution literacy based on mawaris principles among urban Muslim families has the potential to generate injustice and conflict within households. This community service activity aimed to enhance the understanding and awareness of urban Muslim families regarding the importance of applying mawaris principles in family wealth distribution. The activity was conducted at the PKK Women’s Community of Wiyung Brantas Permai on April 19, 2025, involving 23 participants. An educative and participatory approach was employed through interactive lectures, group discussions, case studies, and evaluation using pre-test and post-test instruments. The results indicate an improvement in participants’ understanding of the basic concepts and mechanisms of mawaris, accompanied by changes in attitudes and awareness toward planning family wealth distribution in accordance with Islamic principles. The activity also received positive responses from participants and has the potential to generate sustainable impact through the strategic role of women within the family. Thus, this community service initiative contributes to strengthening Islamic financial literacy and promoting equitable wealth distribution in urban Muslim communities.